Avaliação das áreas de conflito de uso em APP na microbacia do ribeirão Morro Grande - Nardini, Rafael Calore; Campos, Sergio [UNESP]; Ribeiro, Fernanda Leite; Gomes, Luciano Nardini; Felipe, Andrea Cardador; Campos, Mariana de (My University, 2015)
The conflictive areas defined by inappropriate land use see causing serious problems to the environment, resulting in ecological imbalance and wear of natural resources, especially when referring to the permanent preservation areas, which have fundamental importance for balance ecosystems and preservation of water resources. Environmental planning in watershed areas is a key factor on the part of man for the effects to the environment are the lowest possible. This study aimed to evaluate land use conflicts in permanent preservation areas in the watershed stream Morro Grande, Bofete (SP) using Geographic Information System and satellite image of LANDSAT - 5 of 2010, scale 1:50000. The results showed that areas of 330.12ha of permanent preservation, 69.75ha are conflicting, especially for pasture (85.93%) and reforestation (13.55%). The geoprocessing techniques through softwares IDRISI Selva and Cartalinx proved agile and efficient tools and were important in the identification, quantification and editing of maps of land use, permanent preservation and conflict in permanent preservation areas.

As áreas de conflito definidas pelo mau uso do solo vem causando sérios problemas ao meio ambiente, resultando em desequilíbrio ecológico e desgaste dos recursos naturais, especialmente quando se refere às áreas de preservação permanente, que têm importância fundamental para os ecossistemas de equilíbrio e preservação dos recursos hídricos. O planejamento é um fator chave para o controle dos impactos ambientais ao meio ambiente. Este estudo teve como objetivo avaliar os conflitos de uso do solo em áreas de preservação permanente na microbacia hidrográfica do ribeirão do Morro Grande, Bofete (SP), utilizando Sistema de Informação Geográfica e imagens de satélite do LANDSAT – 5 de 2010, em escala 1:50000. Os resultados mostram que dos 330,12ha das áreas de preservação permanente, 69,75ha são conflitantes, sobretudo por pastagem (85,93%) e reflorestamento (13,55%). Os SIG’s IDRISI Selva e Cartalinx juntamente com as técnicas de geoprocessamento demonstraram ágilidade e eficiência na identificação, quantificação e edição de mapas de uso do solo, preservação permanente e de conflitos em áreas de preservação permanente.
Evaluation of the use of conflict areas in app stream Morro Grande watershed
Keywords: Land use; Permanent preservation areas; Geographic information system; Uso do solo; Áreas de preservação permanente; Sistema de Informação geográfica